2014
DOI: 10.21236/ada611580
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Inhibitors of Mechanosensitive Ion Channels as Local Inhibitors of Peripheral Pain

Abstract: Public reporting burden for this collection of information is estimated to average 1 hour per response, including the time for reviewing instructions, searching existing data sources, gathering and maintaining the data needed, and completing and reviewing this collection of information. Send comments regarding this burden estimate or any other aspect of this collection of information, including suggestions for reducing this burden to Department of Defense, Washington Headquarters Services, Directorate for Info… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…However, these studies used gadolinium, a nonselective mechano-gated inhibitor, to block the mechanoreflex during muscle contraction in cats (26,27). We chose to use GsMTx-4, as it is a more selective mechanogated inhibitor than gadolinium and has been shown to inhibit both Piezo1 and Piezo2 channels (4,51). The Piezo protein family, including Piezo1 and Piezo2 channels, comprises rapidly adapting stretch-activated cation channels.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, these studies used gadolinium, a nonselective mechano-gated inhibitor, to block the mechanoreflex during muscle contraction in cats (26,27). We chose to use GsMTx-4, as it is a more selective mechanogated inhibitor than gadolinium and has been shown to inhibit both Piezo1 and Piezo2 channels (4,51). The Piezo protein family, including Piezo1 and Piezo2 channels, comprises rapidly adapting stretch-activated cation channels.…”
Section: Discussionmentioning
confidence: 99%
“…Although this study clearly suggests a role for Piezo channels in the exaggerated mechanoreflex in T1DM rats, it is possible that other mechanically sensitive channels and/or metabolite-induced sensitization of these channels also play a role in evoking the exaggerated mechanoreflex. GsMTx-4 inhibits cationic mechanosensitive channels by forcing them into a closed state with high potency for Piezo and transient receptor potential (TRP) channel families (11,51,54). Specifically, intradermal injection of GsMTx-4 into the rat hindpaw reversed inflammation-induced mechanical hyperalgesia, possibly via decreased sensitization of C-fibers, by inhibiting stretch-activated TRPC1 and TRPC6 channels (2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…GsMTx4 inhibits these channels by inserting into the lipid bilayer at the channel-membrane interface and "pushing" the channel to a closed state (43). Importantly, GsMTx4 inhibits both Piezo1 (4,5,26) and Piezo2 (33), with at least some selectivity for Piezo channels because it did not inhibit mechano-gated TREK-1 channels (5). Our finding that 10 g of GsMTx4 did not inhibit metabolically sensitive receptors in the present study is important because GsMTx4 has been reported to exert off-target effects.…”
Section: Discussionmentioning
confidence: 99%